22.4k views
1 vote
Differentiating Exponential functions In Exercise,find the derivative of the function. See Example 2 and 3.

y = xex - 4e - x

User Fiil
by
5.5k points

1 Answer

5 votes

Answer: The derivative would be
y'=e^x(1+x)+4e^(-x)

Explanation:

Since we have given that


y=xe^x-4e^(-x)

as we know the product rule:


xe^x=x'e^x+xe^x'=e^x+xe^x

so, it becomes,


y'=e^x(1+x)-4* -1e^(-x)\\\\y'=e^x(1+x)+4e^(-x)

Hence, the derivative would be


y'=e^x(1+x)+4e^(-x)

User Ravinder Gujiri
by
6.2k points